Formulation of hair straightening cream from keratin protein - Suguna , Jeganathan (2015)
A research was conducted on the formulation of hair straightening cream from keratin protein. The keratin that used in this formulation was extracted from chicken feathers. The keratin plays an important role during the hair straightening process in order to straighten the hair and reduce the damaged on the hairs. Our hair consists of mainly keratin but in normal condition the hair consists of alpha keratin. The original configuration of the hair is held in place by the bonding found in the cortex layers of the hair. There are four types of bonds which are hydrogen bond, sugar bond, cystine bond, disulphide bond and salt bond. The hair straightening cream will break the disulphide bonds in the hair during the hair straightening process and allowed the confirmation of the new disulphide bonds with the new arrangement, thus giving the hair a new shape. The formulation was made with the mixture of water based and oil based chemicals. Firstly, the oil based and water based mixture were prepared separately at temperatures 60-70 °C. After the mixture was soluble, the water based mixture poured into the oil based mixture at a temperature around 60-70 °C. The mixture then stirred immediately until the temperature dropped to 40 °C. Finally the keratin protein and the fragrance were added into the mixture and the mixture was continuously stirred at room temperature for 2 hours. The result shows that, the formulation has the ability to permanently straighten the hair without the damage to the hair. The SEM analysis proven that the keratin can reduce the damaged to the hair during the straightening process. The characterisation test to the hair straightening cream like pH analysis, colour analysis, centrifuge test, FTIR test, viscosity test, and cycle test (freeze and thaw) shows that the cream is stable and within the standard range. Chicken feather is one of the important source of keratin. This is a good idea because poultry feathers are dumped, used for land filling, incinerated or buried which involves problem in storage, handling, emission control and ash disposal. Therefore, the use of the chicken feather in this project can reduce the waste disposal of the chicken feathers.